Hungarian–South Slavic film relations: An introduction - Szíjártó, Imre (Slavica, 2024)
This study is an introduction to a larger work on Hungarian and Southern Slavic film relations. After reviewing the theoretical and conceptual considerations, the paper attempts to interpret the concepts of national film and transnational film, and it also outlines the types of Hungarian–Slovenian, Hungarian–Croatian, and Hungarian–Serbian film relations. Thus, from the Southern Slavic community, the study focuses on Slovenian, Croatian, and Serbian culture and film. Films from Bosnia and Herzegovina, Bulgaria and Northern Macedonia, and their Hungarian dimensions are also referenced, but the primary focus is the film culture of the three countries neighboring Hungary.